Phenotypic and molecular genetic studies on draughtability in Umblachery breed of cattle - M Kousalya Devi; S M K Karthickeyan; S N Sivaselvam; R Venkataramanan; K G Tirumurugaan (Journal of Livestock Biodiversity, 2025)
A study was conducted to assess the draught potential of Umblachery cattle of Tamil Nadu. Phenotypic traits related to draughtability and their associations with 16 SNPs in six candidate genes (ACE, ADRB2, BDKRB2, GPX-1, IGF-1 and VEGFA) and